Hydrogel Film Assembly Process at Droplet Interface with Evaporation Temperature. Issue 7 (19th February 2019) - Kang, Giho; Seong, Baekhoon; Gim, Yeonghyeon; Lee, Hyungdong; Ko, Han Seo; Byun, Doyoung
Abstract: Recently, thin‐film assembly at the liquid–air interface has been widely studied. These film scaffolds have high potential to control the crystallization process and fabricate single crystals. However, there have been limitations in understanding and controlling the behavior of polymer chains form into films. This study investigates thin‐film assembly at the hydrogel droplet interface with internal flow and its role. During the hydrogel film formation, the internal flow of the droplet is visualized using micro‐particle image velocimetry technique at various temperatures. From the droplet evaporation, convection flow induced by heat cause buoyancy effect and pressure on the interface film from evaporation flux affect the film morphology and its mechanical characteristics. Therefore, more dense assembled film is generated on the droplet interface. It is expected that the investigations could give better understanding of interface film assembly and controlling its properties. Abstract : Hydrogel film assembly becomes denser and shows higher mechanical properties with controlling the evaporation at droplet air–liquid interface. Change of its nanoscaffold structures is measured with X‐ray diffraction scans and images are visualized by scanning electron microscopy. Further, internal flow inside the droplet during evaporation process is visualized with particle image velocimetry to analyze the effect at interface film assembly.